The Influence of Ownership Structure on Accrual Earnings Management in Indonesian Companies: Pre- and Post-COVID 19 Impact - Mardianto; jaslyn (Accounting Department, Faculty of Business and Management, Universitas Internasional Batam, 2024)
Investigating the impact of the COVID-19 pandemic on the relationship between ownership structure and earnings management strategies of Indonesian companies listed in the LQ 45 index is the objective of this study. The primary focus is on how ownership concentration, managerial, institutional, and family ownership affect Accrual Earnings Management (AEM) before and after the pandemic period. Employing multiple linear regression, the research evaluates the effects of these ownership characteristics on AEM in both pre-COVID and post-COVID periods. The study reveals that a dramatic changes of the landscape effect of ownership structure toward AEM. The findings provide valuable insights into how ownership structures influence earnings management during economic crises, offering guidance for regulators and policymakers in overseeing earnings practices. Investigating the impact of the COVID-19 pandemic on the relationship between ownership structure and earnings management strategies of Indonesian companies listed in the LQ 45 index is the objective of this study. The primary focus is on how ownership concentration, managerial, institutional, and family ownership affect Accrual Earnings Management (AEM) before and after the pandemic period. Employing multiple linear regression, the research evaluates the effects of these ownership characteristics on AEM in both pre-COVID and post-COVID periods. The study reveals that a dramatic changes of the landscape effect of ownership structure toward AEM. The findings provide valuable insights into how ownership structures influence earnings management during economic crises, offering guidance for regulators and policymakers in overseeing earnings practices.